فعالية استخدام وسيلة التقييم كويزيز لتعليم مهارة القراءة بمدرسة الثانوية نهضة العلماء كريسيك - Rahma, Anisyah Mauliddini; Machmudah, Umi (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2024)
In this study, researchers used Quizizz in learning reading skills for class VIII MTs NU Gresik. The aims of this study were: To find out the effectiveness of Using Quizizz at MTs NU 1 Gresik. This study uses quantitative approach in the form of an experimental method. The results of this study is The observation results show that by learning using Quizizz, students can be more enthusiastic about working on evaluation questions and increase their scores. As for the hypothesis by using a two-variable comparison test, namely using the Mann-Whitney, the researcher obtained data that the significance value was 0.000 <0.05. Based on the interpretation of the results of the Mann-Whitney test, Ho is rejected and H1 is accepted. In addition, the results of the N-gain test score above show that the average N-gain score of the experimental group is 88%. Therefore it can be concluded that maharah qira'ah learning using quizizz at Mts NU 1 Gresik is effective. في هذه البحث، استخدمت الباحثة كويزيز في تعليم مهارة القراءة للفصل الثامن في المدرسة الثانوية نهضة العلماء كريسيك. أهداف هذا البحث هي: لمعرفة فعالية تعليم مهارة القراءة باستخدام كويزيز في المدرسة الثانوية نهضة العلماء كريسيك. استخدمت الباحثة في هذا البحث بمنهج الكمي في شكل منهج تجريبي. نتائج هذا البحث هيتظهر نتائج الملاحظة أنه من خلال التعلم باستخدام كويزيز ، يمكن للطلاب أن يكونوا أكثر حماسًا للعمل على أسئلة التقييم وزيادة درجاتهم. أما عن الفرضية باستخدام اختبار المقارنة ذي المتغيرين وهما اختبار مان ويتني فقد حصل الباحثة على بيانات أن قيمة الدلالة كانت 0.000 <0.05. بناءً على تفسير نتائج اختبار مان ويتني، تم رفض Ho وقبول Ha. بالإضافة إلى ذلك ، تظهر نتائج اختبار -gain N أعلاه أن متوسط ​​درجة -gain N للمجموعة التجريبية هو 88٪. لذلك يمكن استنتاج أن تعليم مهارة القراءة باستخدام كويزيز في المدرسة الثانوية نهضة العلماء 1 كريسيك فعال.